2023
DOI: 10.3389/fpls.2023.1270304
|View full text |Cite
|
Sign up to set email alerts
|

Responses of community traits and soil characteristics of Achnatherum inebrians-type degraded grassland to grazing systems in alpine meadows on the Qinghai-Tibet Plateau

Yanzhu Chen,
Changlin Xu,
Kaikai Ma
et al.

Abstract: IntroductionScientific grazing management is of great significance for the ecological health and sustainable use of alpine meadows.MethodsTo explore appropriate management methods of alpine grasslands of the Qinghai-Tibet Plateau degraded by Achnatherum inebrians (Hance) Keng ex Tzvele presence, we studied the effects of different grazing systems on the A. inebrians population, grassland vegetation community traits, soil characteristics and soil microbial community structure for cold- season grazing plus suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Drunken horse grass (Achnatherum inebrians) is a common poisonous grass in the Poaceae, and it is widely distributed in the natural grasslands of Northern China [4][5][6]. Studies have shown that this species has invaded more than 85% of the land in some severely degraded areas [7][8][9]. A. inebrians grows rapidly on grasslands, and it competes with other plants for space to grow, nutrients, water, and other resources, which leads to degradation of the grassland and a decrease in high-quality forage [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Drunken horse grass (Achnatherum inebrians) is a common poisonous grass in the Poaceae, and it is widely distributed in the natural grasslands of Northern China [4][5][6]. Studies have shown that this species has invaded more than 85% of the land in some severely degraded areas [7][8][9]. A. inebrians grows rapidly on grasslands, and it competes with other plants for space to grow, nutrients, water, and other resources, which leads to degradation of the grassland and a decrease in high-quality forage [10,11].…”
Section: Introductionmentioning
confidence: 99%